A review of traditional Chinese medicine intervention methods for depression among college students - Yao, Xiyong; Xu, Chen; Yang, Linlin; Wu, Ailin; Xiong, Lin (Frontiers in Psychology, 2025)
Depression has become the most prevalent psychological issue among college students, necessitating urgent intervention measures. Traditional Chinese Medicine (TCM) boasts a long history in the prevention and treatment of psychological and emotional disorders, encompassing non-pharmacological therapies (such as TCM health exercises, Tai Chi, Wu Qin Xi, Ba Duan Jin, acupuncture, etc.) and pharmacological treatments. Key research findings indicate that these TCM interventions can significantly alleviate depressive symptoms and improve sleep quality in college students. However, the studies also acknowledge certain limitations, including varied effectiveness of interventions among individuals and the need for professional diagnosis and treatment in the case of acupuncture and herbal remedies. This provides early prevention and intervention measures for the treatment of depression among college students, and promotes the inheritance of traditional Chinese culture.